Trees as templates for trophic structure of tropical litter arthropod fauna - Kaspari, M. (2013)
Litter arthropod abundance in tropical forests is patchily distributed in space and time. This patchiness can be described by three general hypotheses relating plant-based effects to litter arthropod distribution. The tree hypothesis (H1) posits that environments maintained underneath tree canopies are different from those between canopies in ways that shape arthropod abundance. The species hypothesis (H2) refines this scenario, positing that different plant species might maintain distinct litter environments to which arthropod abundances respond. Without regard to specific plant effects, seasonal changes in litter profiles (H3) can account for temporal patchiness in arthropod abundance. The ecosystem size hypothesis provides a mechanism for tree, species and seasonal effects. It links increasing food chain length with habitat availability and its heterogeneity. In a Panamanian rainforest we sampled litter arthropods in quadrats located near (1 m) and far away (30 m) from the parent trunk of 93 tree individuals (to test the tree hypothesis) from 10 tree species (to test the species hypothesis) in the early wet season, when litter is deepest. To test for effects of seasonal changes of litter profiles, we then resampled 25 trees (i.e., five individuals from each of five species) in the late wet season, when climatic conditions are similar, but litter is shallowest. We found weak support for all tree, species and seasonality hypotheses. With few exceptions, trees and species did not sustain different arthropod abundances, neither early nor late in the wet season. Collembola abundance increased late in the wet season, when litter is shallowest. Supporting the ecosystem size hypothesis, accumulated litter either due to trees, species and seasonality sustained higher predator abundance and higher predator to prey ratios. Our results suggest that plants may account for detrital, brown, food web structure; but these effects are mostly through plant-based provision of structural support. This study adds to growing evidence relating the ecosystem size hypothesis to litter environments and suggest a framework to understand plant-based bottom-up forces in structuring litter communities. © 2013 Elsevier Ltd.